2017
DOI: 10.1016/j.biortech.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Indispensable role of biochar-inherent mineral constituents in its environmental applications: A review

Abstract: Biochar typically consists of both carbon and mineral fractions, and the carbon fraction has been generally considered to determine its properties and applications. Recently, an increasing body of research has demonstrated that mineral components inherent in biochar, such as alkali or alkaline earth metals in the form of carbonates, phosphates, or oxides, could also influence the properties and thus the applications. The review articles published thus far have mainly focused on multiple environmental and agron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(123 citation statements)
references
References 97 publications
6
103
0
1
Order By: Relevance
“…in which the mineral fraction predominates. 6,40 In the present study, the physicochemical properties that were most closely correlated with the parameters of the breakthrough curves (q e , t b , t e ) were %C, %N and %ash (Table S1). The highest positive correlation was found with the %ash, e.g.…”
Section: Comparison Of Copper Sorption On Different Types Of Biocharsupporting
confidence: 54%
See 1 more Smart Citation
“…in which the mineral fraction predominates. 6,40 In the present study, the physicochemical properties that were most closely correlated with the parameters of the breakthrough curves (q e , t b , t e ) were %C, %N and %ash (Table S1). The highest positive correlation was found with the %ash, e.g.…”
Section: Comparison Of Copper Sorption On Different Types Of Biocharsupporting
confidence: 54%
“…In the present study, copper retention was highest in samples with an O/C molar ratio higher than 0.3 and high ash and phosphorus contents, above 40% and 3 g PO kg -1 , respectively (Table 1). As indicated by Xu et al 40 , the formation of metal carbonates and phosphate precipitates is favored in mineralrich biochars. Uchimiya et al 41 , also indicated that heavy metals retention by biochar is enhanced in low carbonized biochar materials.…”
Section: Comparison Of Copper Sorption On Different Types Of Biocharmentioning
confidence: 89%
“…Both biochars were alkaline with high pH values (Table 1, 11.43 for CMB and 11.55 for M-CMB), suggesting that it would potentially remove heavy metals from acid mine drainage [24]. This was correlated to ash content, since the content of ash showed a positive correlation with the alkalinity of bicohar, as observed by many researchers [20,25,26]. High content of ash was also partly reflected by the SEM observations exhibiting many impurities on the surface of biochars ( Figure 1).…”
Section: Biochar Propertiessupporting
confidence: 52%
“…Agrafioti et al [24] obtained similar results and suggested biochar produced at low temperature could be more suitable to agricultural use rather than that derived from high temperature. Considering the more volatile loss and bioavailability reduction of mineral nutrients at high pyrolysis temperatures [37], it may be thus recommended that municipal sewage sludge be converted into biochar at low temperature, e.g., 200 • C, and then used as a nutrient supplement for urban soil. Moreover, a few studies have shown that the biochar derived from lignocellulosic materials has the ability to ameliorate soil physical parameters such as pore size, proportion of water-stable aggregates, bulk density, water retention, etc.…”
Section: Urban Soil Improvement Following Sewage Sludge Biochar Additionmentioning
confidence: 99%